Strategi Pembelajaran Discovery Learning pada Mata Pelajaran Akidah Akhlak - Arlina; Hasibuan, Raudhatul Ma'wa; Mulyani, Nining; Lesmana, Baron; Harahap, Rizky Nia (At-Tadris: Journal of Islamic Education, 2023)
Discovery learning learning strategy which is a learning strategy that directs students to be more active and think critically in learning so that they can solve a problem related to the existing subject matter. The research method used is descriptive qualitative research and the technique used uses interview techniques. Qualitative descriptive research produces information in the form of quality and reliable data and can be accounted for its authenticity. It can be concluded that One of the benefits of discovery learning is that it helps students develop their critical thinking skills. Another benefit is that it helps students become more independent because they can use their own initiative and creativity to overcome existing challenges. If the teacher can effectively explain, manage, and direct the pupils, then the existing deficiencies can be corrected. Therefore, in order to use this discovery learning technique successfully and efficiently, the teacher must first understand the basic principles.